1978
DOI: 10.1073/pnas.75.8.4011
|View full text |Cite
|
Sign up to set email alerts
|

A factor from neurons increases the number of acetylcholine receptor aggregates on cultured muscle cells.

Abstract: There is an increase in the number of acetylcholine (AcCho) receptor aggregates on striated embryonic mouse myotubes when they are cocultured with clonal neuroblastoma-glioma hybrid cells. Medium conditioned by hybrid cells contains a factor which increases the number of AcCho receptor aggregates on myotubes cultured from mouse, rat or chick muscle. AcCho receptor-aggregating activity was present in medium conditioned by the neuroblastoma parent clone but was not detected in medium conditioned by cells of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(63 citation statements)
references
References 29 publications
2
61
0
Order By: Relevance
“…It was found that addition of rat embryonic brain and spinal cord extracts to the culture increased the number ofAcCho receptors and AcCho receptor aggregates on the cell surface ofa rat muscle cell line and on primary chicken myotubes (5,6). Similarly, medium conditioned by a hybrid neuroblastoma cell line induced aggregation ofAcCho receptors on the surface ofcultured myotubes (7). These findings suggest that nerve termini release neurotrophic substances that may be responsible for the redistribution of AcCho receptors.…”
mentioning
confidence: 64%
“…It was found that addition of rat embryonic brain and spinal cord extracts to the culture increased the number ofAcCho receptors and AcCho receptor aggregates on the cell surface ofa rat muscle cell line and on primary chicken myotubes (5,6). Similarly, medium conditioned by a hybrid neuroblastoma cell line induced aggregation ofAcCho receptors on the surface ofcultured myotubes (7). These findings suggest that nerve termini release neurotrophic substances that may be responsible for the redistribution of AcCho receptors.…”
mentioning
confidence: 64%
“…NG108-15 cells form functional cholinergic synapses on myotubes (Christian et al, 1977), and a factor from these cells promotes nAChR clustering (Christian et al, 1978). Coculture of myotubes with NG108-15 cells increases nAChR ␤ subunit tyrosine phosphorylation (K. Miles, unpublished observations), a phosphorylation pattern shared by mature nAChRs in the neuromuscular junction (Qu et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have also demonstrated repeatedly that although each event is regulated by some aspect of motor nerve-muscle interaction, the types of regulation may vary among the individual events. For instance, clustering ofAcChoR is independent of synaptic transmission, appearing, instead, to be dictated at first by molecules of neuronal origin and ultimately by a component of the muscle's basal lamina (5)(6)(7)(8)(9)(10). On the other hand, the levels of extrajunctional AcChoR and synaptic AcChoE seem to be strongly influenced by synaptic activity (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%